Meeting with my brother : a novella - Yi, Mun-yŏl, 1948- (Weatherhead books on Asia., 2017)
"Narrated in the first person, Meeting with My Brother tells the story of a professor's journey to meet with his younger half-brother from North Korea. The professor's father had left his family behind in the South during the Korean War and eventually had another family in the North. The story includes the professor's negotiations with the go-between who arranges the meeting, his participation in a tour group (the necessary excuse to travel to the area in China where the meeting takes place), his interaction with other tour members and Koreans living in the area, and finally his meeting with his brother. The story includes different positions on reunification and illuminates many of the reasons that make reunification difficult. In this new translation the author has added a new vignette that does not appear in the original."